DETERMINATION AND DEGRADATION PYRENE FROM PAOTERE PORT SEDIMENTS WITH OXIDIZER KMnO4 - Rachma Surya Masnawan; Nursiah La Nafie; Adiba Arief (Hasanuddin University, 2017)
Paotere port is one of port in Makassar which functions as a stopover place of ships, also serves as fish market and fishermen settlements. Various activities of transportation, commerce and households occurred in the Paotere port area can be a source of pollution of pyrene compounds to the surrounding environment. Pyrene compounds that accumulate and can not be degrade will impact the environment and marine life. Determination pyrene in sediment from Paotere Port have been carried out using GC-MS by sonication using dichloromethane as solvent. Result show that there was no PAH in sediment of the three sampling stations. Pyrene compound chemically degradation was conducted by sonication for 1 hour using an oxidant KMnO4 concentration of 0.05 M, 0.07 M and 0.1 M. Results show that KMnO4 as oxidizing agent could to degrade the whole pyrene with concentration of 87,8554 ng/g in sediment.